1993
DOI: 10.1111/j.1467-8624.1993.tb02961.x
|View full text |Cite
|
Sign up to set email alerts
|

The Relations of Emotionality and Regulation to Preschoolers' Social Skills and Sociometric Status

Abstract: The purpose of this study was to examine the relations of emotionality (intensity and negative emotion) and regulation (coping and attentional regulation) to preschoolers' social skills (as rated by adults) and sociometric status. Teachers' ratings of children's constructive coping and attentional control were positively related to boys' social skills and peer status, whereas negative affect was negatively related. Acting out (vs. avoidant) coping and emotional intensity were negatively related to girls' and b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

27
369
6
23

Year Published

2003
2003
2012
2012

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 333 publications
(425 citation statements)
references
References 62 publications
27
369
6
23
Order By: Relevance
“…For example, Eisenberg et al have articulated a conceptual model of the impact of emotion reactivity and emotion regulation on children's functioning (Eisenberg & Fabes, 1992;Eisenberg et al, 2000) based on earlier models proposed by Rothbart and Derryberry (1981) and others. Empirical support for the Eisenberg et al model has been reported in several studies (e.g., Ialongo et al, 2001;Eisenberg et al, 1993;Eisenberg, Fabes et al, 1997).…”
mentioning
confidence: 67%
See 4 more Smart Citations
“…For example, Eisenberg et al have articulated a conceptual model of the impact of emotion reactivity and emotion regulation on children's functioning (Eisenberg & Fabes, 1992;Eisenberg et al, 2000) based on earlier models proposed by Rothbart and Derryberry (1981) and others. Empirical support for the Eisenberg et al model has been reported in several studies (e.g., Ialongo et al, 2001;Eisenberg et al, 1993;Eisenberg, Fabes et al, 1997).…”
mentioning
confidence: 67%
“…Thus, over time, an emotionally reactive and/or poorly regulated child with a predisposition to display speech disfluencies (due to communicative, motoric, linguistic, or situational factors) would be more likely to experience a disfluency problem that persists, than a similarly predisposed child with less reactivity and/or better regulatory abilities. Although at present there is little empirical evidence linking emotional reactivity and regulatory skills to childhood stuttering, there is a substantial body of knowledge Ialongo et al, 2001;Eisenberg et al, 1993; Eisenberg, Fabes et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations